2000
DOI: 10.2190/x8pq-k0gq-t2dr-xy1a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Instructional Efficacy of Computer-Mediated Interactive Multimedia: Comparing Three Elementary Statistics Tutorial Modules

Abstract: This study evaluated three tutorial modules, equivalent in content but different in mode of presentation, for introducing elementary statistics concepts. In a single session, fifty-seven college students participated in one of four randomly assigned conditions: paper-and-pencil, basic computerized, computerized multimedia, or control group. Participants completed a demographic questionnaire, a survey of attitudes toward math and computers, the Personal Need for Structure (PNS) scale, a basic math proficiency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Briand and Hill () show that computer‐assisted teaching of basic econometric concepts and learning by doing are more successful techniques for teaching undergraduate students. Similarly, Gonzalez and Birch () and Moro‐Egido and Pedauga () successfully implemented software instruction to improve students' knowledge acquisition. These positive effects of CAI are reported across many cultural settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Briand and Hill () show that computer‐assisted teaching of basic econometric concepts and learning by doing are more successful techniques for teaching undergraduate students. Similarly, Gonzalez and Birch () and Moro‐Egido and Pedauga () successfully implemented software instruction to improve students' knowledge acquisition. These positive effects of CAI are reported across many cultural settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, while it was hypothesised that the same themes that emerged in the study by Neumann et al (2008) would also be found, it was also expected that additional themes relevant to student learning would be identified. Several processes have been suggested to be important in technology based learning, including information processing learning processes (González & Birch, 2000), visual learning (Davis & Bostrom, 1992;Psotka, Kerst & Westernman, 1993), cognitive style (Carlson, 1991;Riding & Douglas, 1993), communication (Kuehn, 1994), self-efficacy (Ertmer, Evenbeck, Cennamo & Lehman, 1994), and motivation (Lens, 1994). As such, it was hypothesised that some of these themes would also emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the considerable efforts made by educational researchers and statistics instructors, students have been found to still hold misconceptions after following a reformed course (González and Birch 2000;Chance, delMas, and Garfield 2004;Scheines, Leinhardt, Smith, and Cho 2005;delMas, Garfield, Ooms, and Chance 2007). In order to enlarge the research base for the construction of powerful learning environments for statistics, new research studies should focus on two aspects.…”
Section: Introductionmentioning
confidence: 99%